Infection of cord blood monocyte-derived macrophages with human immunodeficiency virus type 1. - Ho, W Z (1992)
We have investigated the susceptibility of cord blood monocyte-derived macrophages to human immunodeficiency virus type 1 (HIV-1) infection in vitro. Cord blood monocytes were maintained in vitro for 10 to 15 days and then infected with HIV-1. Syncytia were observed 14 days after infection by light microscopy. Viral proteins were detected by immunofluorescence assay. Electron microscopic examination demonstrated typical lentivirus particles within cytoplasmic vacuoles. The supernatants from the HIV-1-infected cultures also contained significant reverse transcriptase activity and p24 antigen. Like adult monocyte/macrophages, cord-derived monocyte/macrophages expressed the CD4 receptor molecule. Pretreatment with blocking antibody prior to infection with HIV-1 Bal significantly reduced or blocked infection of cord monocyte/macrophages. When cord and adult monocyte/macrophages were infected with HIV-1 Bal or Ada-M and directly compared, higher reverse transcriptase activities and p24 antigen expression were obtained with cord monocyte/macrophages. However, no significant difference was found between adult and cord monocyte/macrophages infected with HIV-1 IIIB. These observations suggest that cord monocyte-derived macrophages may be important in the pathogenesis of pediatric AIDS and that the increased susceptibility of cord monocyte/macrophages to HIV-1 infection in vitro may be relevant to the enhanced susceptibility of neonates to HIV-1 diseases in vivo.